Selective sharing of news items and the political position of news outlets - Julian Freitag; Anna Kerkhof; Johannes Münster (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
We present an easy to implement measure for the political position of news outlets based on politicians' selective sharing of news items. Politicians predominantly share news items that are in line with their political position, hence, one can infer the political position of news outlets from the politicians' revealed preferences over news items. We apply our measure to twelve major German media outlets by analyzing tweets of German Members of Parliament (MPs) on Twitter. For each news outlet under consideration, we compute the correlation between the political position of the seven parties in the 19th German Bundestag and their MPs' relative number of Twitter referrals to that outlet. We finnd that three outlets are positioned on the left, and two of them are positioned on the right. Several robustness checks support our results.
Keywords: H41; L82; L86; P16; 330; political media bias; political position; selective sharing; social media; Twitter